Biomarkers in saliva for the detection of oral squamous cell carcinoma and their potential use for early diagnosis: a systematic review (2015)
Objective To determine the capacity of salivary biomarkers in the early diagnosis of oral squamous cell carcinoma. Study design A systematic review of the literature was performed based on the English titles listed in the PubMed, EBSCO, Cochrane, Science Direct, ISI web Science and SciELO databases using the following search descriptors: Oral cancer, diagnosis, biomarkers, saliva and oral squamous cell carcinoma. Abstracts and full-text articles were assessed independently by two reviewers. International checklists for assessment of methodological quality were used. Levels of evidence and grades of recommendation through the Scottish Intercollegiate Guidelines Network (SIGN) template were recognized. The units of analysis were identified through a reference matrix. Results Through the research strategy and after application of different filters and considering choosing criteria, six studies were obtained for analysis. Salivary biomarkers for oral cancer most frequently found were mRNA and proteins for IL-8, CD44, MMP-1 and MMP-3. New peptidebiomarkers such as Cyfra 21-1 and ZNF510 were found. ZNF 510 was the only biomarker which increased in the population with tumour stage T1 + T2 and T3 + T4. Only one study showed a sensitivity and specificity of 96% when the biomarker ZNF 510 is employed to discriminate early and late tumour stages. Conclusions There is no sufficient scientific evidence to support the capacity of the identified salivary biomarkers for the early diagnosis of oral cancer (sub-clinical stages of the pathogenic period before cancer phenotypes are manifested). Salivary biomarkers, however, may be employed to discriminate between healthy and cancer patients.